If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3 + -1(2x + -8) = 9 Reorder the terms: 3x + 3 + -1(-8 + 2x) = 9 3x + 3 + (-8 * -1 + 2x * -1) = 9 3x + 3 + (8 + -2x) = 9 Reorder the terms: 3 + 8 + 3x + -2x = 9 Combine like terms: 3 + 8 = 11 11 + 3x + -2x = 9 Combine like terms: 3x + -2x = 1x 11 + 1x = 9 Solving 11 + 1x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 1x = 9 + -11 Combine like terms: 11 + -11 = 0 0 + 1x = 9 + -11 1x = 9 + -11 Combine like terms: 9 + -11 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 5x-2x-9=40 | | -2+44x=130 | | 100c+8=75c+10 | | 42=.33(b)(6) | | 7x-14b+b(5-x)+4bx=10x-3(2b+x) | | U+-10=2 | | (x+10)(x-3)=25 | | h^2-5h-30=0 | | y-40+3=-40 | | 100-a=10% | | 9x-9=x | | (7-8)x=-29 | | -16=2v+8 | | x^4-y+xy-x^3=0 | | 10-a=10% | | Log(x-6)=2.75 | | 2x+5th=75 | | (1+u)(5u-8)=0 | | 8w=218 | | 11y+y= | | 15x-3(x+4)=6 | | 2(4x-6)=48 | | 4x^2-10=15 | | 32-t^5=0 | | 8a+4x=47fora | | 12(-4+6x)=13x+23(x+9) | | 2x+16=7x | | 6t-5=-29 | | 40=5(2Y+10) | | 8b-7b= | | y-3=9(x-0) | | 3y-5x=12+5y |